PERANCANGAN METRIK DAN PENGUKURAN KINERJA RANTAI PASOK DI PT SIERAD PRODUCE, TBK. - Revi Agustian (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
The competition maps of the industry will change from one country to be the ASEAN regional in 2015 as the commencement of globalization in the ASEAN Economic Community. Performance of supply chain will become more strategic for domestic companies to increase their competitiveness. The approach used for designing and measuring of supply chain performance is the SCOR model which is a processbasedmodels. The model integrates three key elements in the management namely business process reengineering,benchmarking, and process measurement into a cross-functional framework in supply chain. The research was carried out with a case study at PT Sierad Produce, a feedmill industry in East Java, Indonesia. Based on supply chain business process mapping, resulted 22 design of metrics used for measuring Period I and Period II. The result of measurement found increase of SCOR process performance by 5.3% and attributes performance by 5.6%.